Impacts of the coronavirus pandemic on vocational education and training : snapshots from eight countries - Vantuch, Juraj [Verfasser]; Dembowski, Horacy [Verfasser]; Teräs, Marianne [Verfasser]; Eiríksdóttir, Elsa [Verfasser]; Marhuenda Fluixá, Fernando [Verfasser]; Matseleng Allais, Stephanie [Verfasser]; López Saldana, Rolando [Verfasser]; Pham Viet, Ha [Verfasser] (My University, 2021)
Coronavirus is keeping the world in suspense. Contact restrictions, economic downturns and uncertainty regarding future developments are all creating major challenges for vocational education and training too. How has the COVID-19 pandemic affected vocational education and training? Which educational policy measures or practical solutions have been initiated, and which developments will leave a lasting mark on VET? We put these questions to VET experts from eight countries, five of which are members of the European Research Review Group (Edge Foundation, UK). Their snapshots provide insights into current developments around the world. (BIBB-Doku)
Auswirkungen der Corona-Pandemie auf die Berufsbildung : Blitzlichter aus acht Ländern
Keywords: S 1 Stufen der Berufsbildung; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; I 2.3.1 Afrika; I 2.3.3 Lateinamerika; I 2.3.4 Asien; 370; Berufsbildung; Berufsausbildung; Pandemie; Auswirkung; Slowakei; Polen; Schweden; Island; Spanien; Südafrika; Vietnam; Mexiko